Anti‐CD19 chimeric antigen receptor‐modified T‐cell therapy bridging to allogeneic hematopoietic stem cell transplantation for relapsed/refractory B‐cell acute lymphoblastic leukemia: An open‐label pragmatic clinical trial. Issue 10 (2nd August 2019) - Jiang, Huiwen; Li, Chenggong; Yin, Ping; Guo, Tao; Liu, Lin; Xia, Linghui; Wu, Yaohui; Zhou, Fen; Ai, Lisha; Shi, Wei; Lu, Xuan; Wang, Huafang; et al.
Abstract: Chimeric antigen receptor‐modified T‐cell (CAR‐T) therapy is effective and safe for patients with relapsed/refractory B‐cell acute lymphoblastic leukemia (r/r B‐ALL), but its value has been limited in terms of long‐term leukemia‐free survival. New strategies that can help CAR‐T therapy achieve lasting effect are urgently warranted. This non‐randomized interventional pragmatic clinical trial had a particular aim. It explored whether consolidative allogeneic hematopoietic stem cell transplantation (allo‐HSCT) could improve the long‐term prognosis of the minimal residual disease‐negative complete remission (MRD − CR) patients after CAR‐T therapy. In the first stage, 58 r/r B‐ALL patients received split doses of CAR‐T cells after lymphodepleting chemotherapy, and 51 (87.9%) achieved CR. In the second stage, 21/47 MRD − CR patients without previous allo‐HSCT and contraindications or other restrictions, on their own accord, received consolidative allo‐HSCT within three months after CAR‐T therapy. There was no difference in overall survival (OS) between the MRD − CR patients who received allo‐HSCT and those who did not. However, event‐free survival (EFS) and relapse‐free survival (RFS) were significantly prolonged by allo‐HSCT in the subgroups. This was with either high (≥5%) pre‐infusion bone marrow MRD assessed by flow cytometry (BM‐FCM‐MRD) or poor prognostic markers ( P < .05). However, no difference was found in EFS and RFS for patients with pre‐infusion BM‐FCM‐MRD <5% and without poor prognostic markers ( P > .05). To conclude, CAR‐T therapy bridging to allo‐HSCT is a safe and effective therapeutic strategy for r/r B‐ALL patients, and may prolong their EFS and RFS, especially when they have high pre‐infusion BM‐FCM‐MRD or poor prognostic markers.